Review of findings in prophylactic gynaecological specimens in Lynch syndrome with literature review and recommendations for grossing. Issue 2 (16th April 2014) - Downes, Michelle R; Allo, Ghassan; McCluggage, W Glenn; Sy, Keiyan; Ferguson, Sarah E; Aronson, Melyssa; Pollett, Aaron; Gallinger, Steve; Bilbily, Elaine; Shaw, Pat; Clarke, Blaise A
<x xml:space="preserve">Abstract</x> Aims Prophylactic hysterectomy with bilateral salpingo‐oophorectomy is being increasingly undertaken in patients with Lynch syndrome (LS). The pathological features in such specimens are not well described and, unlike the SEE‐FIM protocol for salpingo‐oophorectomy specimens in BRCA1/2 mutation carriers and the gastrectomy grossing protocols for patients with CDH1 (E‐cadherin) mutations, guidelines have not been devised for the grossing of prophylactic gynaecological specimens from LS patients. We aimed to review the pathological findings in a series of prophylactic gynaecological specimens from LS patients and develop guidelines for the grossing of these specimens. Methods and results We reviewed the pathological findings in 25 prophylactic gynaecological specimens from LS patients and audited the grossing protocols in different centres across Ontario, Canada. We found a 32% incidence of endometrial carcinoma or a precursor lesion; the two endometrial cancers identified were low‐grade, low‐stage endometrioid adenocarcinomas. To address the absence of guidelines for pathological examination, we undertook a literature review of gynaecological malignancies and incidental findings in prophylactic specimens in LS patients. Conclusion We provide recommendations regarding the grossing of such specimens which includes in‐toto examination of the lower uterine segment, endometrium, ovaries and fallopian tubes with representative sampling of the cervix.